A study on COVID-19-related stigmatization, quality of professional life and professional identity in a sample of HCWs in Italy - Caricati, Luca; D'Agostino, Grazia; Sollami, Alfonso; Bonetti, Chiara (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Perceived COVID-19-related stigmatizations have a strong impact on healthcare workers’ wellbeing and quality of professional life, decreasing satisfaction and increasing fatigue. This work aims to investigate the role of professional identification in moderating the impact of COVID-19-related stigma on quality of professional life in a sample of healthcare professionals working in hospital. Methods: A cross-sectional design in which a web-based questionnaire was sent to professionals was used to collect answers from 174 participants, most of whom women and nurses. Results: Perceived stigma was negatively related with compassion satisfaction and positively related with an increase in both burnout and secondary traumatic stress. Professional identification had a positive correlation with satisfaction and a negative correlation with burnout, but this was not directly related with secondary traumatic stress. Importantly, stigma and identification interacted so that stigma decreased compassion satisfaction only when identification was low, and increased secondary traumatic stress only when identification was high. No interaction effect appeared with respect to burnout. Conclusions: Experience of stigmatization has the potential to decrease the quality of professional life of healthcare professionals. Professional identification seems to help professional to maintain higher level of compassion satisfaction and reduced burnout. However, professional identification seems also be associated with vicarious trauma experienced following stigma. (www.actabiomedica.it)